The CIO edge seven leadership skills you need to drive results - Waller, Graham (Harvard Business press, 2010)
Sure, It leaders need technological savvy and business acumen to understand and contribute to their company's goals. But the best of them possess a far more potent ability: They forge superior working relationships companywide to collaboratively deliver business results.